SISTEM KERJA DAN HUBUNGAN SOSIAL KARYAWAN NASI AMPERA LINTAU DI KOTA PEKANBARU - Nur Rahma Dini; Yessi " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT The number of hours worked is the length of time in hours spent working the entire job. Working hours at each place and location have their own policies. The Nasi Ampera Lintau restaurant is one of the restaurants that has 12 (twelve) hours of work for its employees. This research was conducted at the Nasi Ampera Lintau restaurant in the city of Pekanbaru, Riau province. The aims of this study were to find out: 1) the purpose of working 12 hours at the Nasi Ampera Lintau restaurant, 2) the social relations that occurred between Nasi Ampera Lintau employees during 12 hours of work. This research uses descriptive qualitative method. The data collection techniques of this research were in-depth interviews, observation, and documentation. Based on the results of the study, it can be concluded that: 1) the work activities of the employees of the Nasi Ampera Lintau restaurant are divided into three parts, namely the trough, the middle and back, and the cashier, 2) the social relations that occur in the employees of the Nasi Ampera Lintau restaurant are in the form of social relations. associative and dissociative, the form of associative relationships that occur is a form of cooperation. Meanwhile, dissociative social relations are conflict and competition. 3) social action taken by employees who work for 12 (twelve) hours at the Nasi Ampera Lintau restaurant is an instrumental rational social action (zwerk rational), where employees consciously work for 12 (twelve) hours in order to earn wages. or salary received to meet the needs of life, and value rational action where employees apply an honest and responsible attitude when working. Keywords: work system, social action, restaurant employees